SATB1-Binding Sequences and Alu-Like Motifs Define a Unique Chromatin Context in the Vicinity of Human Immunodeficiency Virus Type 1 Integration Sites - Kumar, Pavan P. (American Society for Microbiology, 2007)
Retroviral integration has recently been shown to be nonrandom, favoring transcriptionally active regions of chromatin. However, the mechanism for integration site selection by retroviruses is not clear. We show here the occurrence of Alu-like motifs in the sequences flanking the reported viral integration sites that are significantly different from those obtained from the randomly picked sequences from the human genome, suggesting that unique primary sequence features exist in the genomic regions targeted by human immunodeficiency virus type 1 (HIV-1). Additionally, these sequences were preferentially bound by SATB1, the T lineage-restricted chromatin organizer, in vitro and in vivo. Alu repeats make up nearly 10% of the human genome and have been implicated in the regulation of transcription. To specifically isolate sequences flanking the viral integration sites and also harboring both Alu-like repeats and SATB1-binding sites, we combined chromatin immunoprecipitation with sequential PCRs. The cloned sequences flanking HIV-1 integration sites were specifically immunoprecipitated and amplified from the pool of anti-SATB1-immunoprecipitated genomic DNA fragments isolated from HIV-1 NL4.3-infected Jurkat T-cell chromatin. Moreover, many of these sequences were preferentially partitioned in the DNA associated tightly with the nuclear matrix and not in the chromatin loops. Strikingly, many of these regions were disfavored for integration when SATB1 was silenced, providing unequivocal evidence for its role in HIV-1 integration site selection. We propose that definitive sequence features such as the Alu-like motifs and SATB1-binding sites provide a unique chromatin context in vivo which is preferentially targeted by the HIV-1 integration machinery.